Autonomi Daerah : Kesan Pelaksanaannya terhadap Perkembangan Sistem Perbankan Islam di Negeri Aceh Darussalam - Mujiburrahman Muhammad Saleh; Nur Shahidah Ab Hamid (Universiti Sains Islam Malaysia, 2024)
e-Proceedings of The 9th Islamic Banking, Accounting and Finance International Conference 2020 (iBAF2020) “Navigating the New Normal in Islamic Finance and Wealth Management” 10th – 11th November 2020, Malaysia Organized by: Faculty of Economics and Muamalat,USIM Page: 192-199